A Feminist Food Justice Reflection on the Politics of Food, Land, and Agriculture in Central America - Arguedas Ramírez, Gabriela (2019)
This volume takes a unique approach, dealing specifically with issues at the intersection of food and agricultural systems, environmental degradation, and climate change. It fills a gap in the literature on food and environmental justice in the context of global climate change offering a scholarly, yet accessible, analysis of the issues.